Does tear size influence factors associated with early retear, satisfaction, and functional outcomes after arthroscopic rotator cuff repair? - Ala’ Hawa; Ahmed F. Hawwa; James Bilbrough; Victor Chen; Mina Shenouda; George A. C. Murrell (PLoS ONE, 2026)
Background Determinants of structural retear, patient satisfaction, and functional outcomes after arthroscopic rotator cuff repair may vary by tear size and influence surgical decision-making. Purpose To determine whether tear size influences factors associated with early structural retear, postoperative satisfaction, and functional outcomes after arthroscopic rotator cuff repair. Study design Cohort study; Level of evidence, 3. Methods A total of 1,166 primary arthroscopic rotator cuff repairs were categorized by mediolateral tear size as small (≤10 mm), medium (11–29 mm), or large (30–50 mm). At 6 months, patients underwent standardized ultrasound evaluation for structural retear and completed a 5-point satisfaction scale. Shoulder strength and range of motion were measured. Multivariable regression analyses were performed separately for each tear size group. Results Associations with structural retear differed by tear size. In small tears, older age, longer operative time, greater anteroposterior tear dimension and preoperative stiffness were associated with increased retear risk, while anchors number showed no association. In medium tears, older age, larger anteroposterior tear dimension, and greater preoperative supraspinatus strength were associated with retear risk, whereas greater number of anchors reduced this risk. In large tears, retear was associated with factors including age, sex, range of motion, and pain at rest, with no association with anchors number. Satisfaction also varied by tear size: greater anchors number was associated with higher satisfaction in small tears, whereas in medium and large tears satisfaction was related to shoulder-related factors. The number of anchors was not consistently associated with postoperative strength or range of motion. Conclusion Factors associated with re-tear, satisfaction and functional outcomes vary by tear size. Greater number of anchors reduced the odds of retear only in medium tears and showed minimal association with functional outcomes, supporting tear size–specific counselling and surgical planning.